Cardiac cholinergic NO-cGMP signaling following acute myocardial infarction and nNOS gene transfer. - Dawson, T; Li, D; Woodward, T; Barber, Z; Wang, L; Paterson, D (2008)
Myocardial infarction (MI) is associated with oxidative stress, which may cause cardiac autonomic impairment. We tested the hypothesis that acute MI disrupts cardiac cholinergic signaling by impairing nitric oxide (NO)-cGMP modulation of acetylcholine (ACh) release and whether the restoration of this pathway following cardiac neuronal NO synthase (nNOS) gene transfer had any bearing on the neural phenotype. Guinea pigs underwent four ligature coronary artery surgery (n = 50) under general anesthesia to induce MI or sham surgery (n = 32). In a separate group, at the time of MI surgery, adenovirus encoding nNOS (n = 29) or enhanced green fluorescent protein (eGFP; n = 30) was injected directly into the right atria, where the postganglionic cholinergic neurons reside. In vitro-evoked right atrial [3H]ACh release, right atrial NOS activity, and cGMP levels were measured at 3 days. Post-MI 24% of guinea pigs died compared with 9% in the sham-operated group. Evoked right atrial [3H]ACh release was significantly (P < 0.05) decreased in the MI group as was NOS activity and cGMP levels. Tetrahydrobiopterin levels were not significantly different between the sham and MI groups. Infarct sizes between gene-transferred groups were not significantly different. The nNOS transduced group had significantly increased right atrial [3H]ACh release, right atrial NOS activity, cGMP levels, and decreased cAMP levels. Fourteen percent of the nNOS transduced animals died compared with 31% mortality in the MI + eGFP group at 3 days. In conclusion, cardiac nNOS gene transfer partially restores the defective NO-cGMP cholinergic pathway post-MI, which was associated with a trend of improved survival at 3 days.